Socio-economic burden of disease: survivorship costs for renal cell carcinoma - Michaeli, Julia; Michaeli, Daniel; Boch, Tobias; Albers, Sebastian; Michaeli, Christoph T. (European journal of cancer care, 2022)
Objective The objective of this study is to assess the risk-stratified 10-year socio-economic burden of renal cell carcinoma (RCC) follow-up costs after initial treatment in Germany from 2000 to 2020. Methods A micro-costing method considering direct and indirect medical expenditure associated with follow-up procedures was employed to calculate survivorship costs per patient. The frequencies of physician-patient visits, examinations and diagnostic tests were extracted from guidelines, whilst expenses were sourced from literature and official scales of tariffs. Societal costs were calculated based on three perspectives: patients, providers and insurers. Results Mean societal 10-year follow-up costs per patient amounted to EUR 3,377 (95%CI: 2,969-3,791) for low-risk, EUR 3,367 (95%CI: 3,003-3,692) for medium-risk and EUR 4,299 (95%CI: 3,807-4,755) for high-risk RCC in 2020. Spending increased by +32% from 2000 to 2020 for low-risk RCC, whilst medium-and high-risk RCC expenditure was cut by −39% and −22%, respectively. Patients shouldered 27%, providers 43% and insurers 35% of costs in 2020. Resources were consumed by medical imaging (52%), physician-patient consultations (31%), travel expenses (17%) and blood tests (1%). Conclusion Results highlight the economic burden cancer survivorship poses for society. Cancer survivors require individualised, evidence-based and insurance-covered follow-up schedules to permit the early detection of side-effects, metastasis and secondary malignancies.